Effects of the grain size and shape on the flow stress: A dislocation dynamics study. (February 2019) - Jiang, Maoyuan; Devincre, Benoit; Monnet, Ghiath
Abstract: Dislocation dynamics simulation is used to investigate the effect of grain size and grain shape on the flow stress in model copper grains. We consider grains of 1.25–10 μm size, three orientations (<135>, <100> and <111>) and three shapes (cube, plate and needles). Two types of periodic aggregates with one or four grains are simulated to investigate different dislocation flux at grain boundaries. It is shown that in all cases the flow stress varies linearly with the inverse of the square root of the grain size, with a proportionality factor varying strongly with the grain orientation and shape. Simulation results are discussed in the light of other simulation results and experimental observations. Finally, a simple model is proposed to account for the grain shape influence on the grain size effect.